Evaluation of Patients Diagnosed with Congenital Glycosylation Defects: A Rainbow of Inherited Metabolic Disorders - Sebile Kılavuz; Fatma Derya Bulut; Deniz Kor; Berna Şeker Yılmaz; Atıl Bişgin; Fadli Demir; Bahriye Atmış; Derya Alabaz; Neslihan Mungan; Mustafa Yılmaz (Çocuk Dergisi)
Introduction: Congenital glycosylation defects (CDGs) manifest with multisystemic symptoms involving the immune, central nervous, endocrine, and musculoskeletal systems. A total of 137 distinct CDG types have been identified to date. Materials and Methods: Patients diagnosed with CDG in the Division of Pediatric Metabolism and Nutrition, at Çukurova University, between 2013 and 2019 were included in the study. The patients’ files were retrospectively reviewed, and demographic, clinical, laboratory and radiological findings and molecular analyses were recorded and evaluated. Results: The mean age at diagnosis for a total of 11 (6 Female; 5 Male) patients (Four with PMM2-CDG, one with MPI-CDG, one with DOLK-CDG, one with B4GALT1-CDG, three with TMEM165-CDG, and one with PIGNCDG) was 6.94 years (ranging from 11 months to 22 years). Amongst the patients, 45% (5 individuals) were male. Sixty-three percent of patients exhibited low weight and height (below the 5th percentile). Elevated liver enzymes were observed in 82% of cases, while 82% showed neurodevelopmental delay, 72% had cerebellar atrophy, and 72% experienced growth retardation. Additionally, 73% of patients displayed hepatomegaly and thrombocytopenia, and 63% had renal involvement. An homozygous p.V129M (c.385G>A) mutation in the PMM2 gene confirmed PMM2-CDG diagnosis in four patients. Furthermore, distinct homozygous mutations were detected: p. I399T (c.1193T>C) in the MPI gene, p. Y441S (c.1322A>C) in the DOLK gene, p. Arg126Cys (c.376C>T) in the TMEM165 gene, a novel p. Tyr239* (c.717T>G) mutation in the B4GALT1 gene, and a novel p. Thr266Ala (c.2356A>G) mutation in the PIGN gene. Conclusion: CDGs exhibit a diverse clinical spectrum, earning them the moniker “the rainbow” of hereditary metabolic disorders. While PMM2- CDG is the most prevalent subtype, only a few instances of other subtypes have been documented. Inverted nipples and abnormal fat pads are primary features of CDGs. The intricate nature of our cases and the rarity of DOLK-CDG, PIGN-CDG, and TMEM-165-CDG diagnoses stand out as notable aspects of this report.